2012
DOI: 10.1007/s00125-012-2456-x
|View full text |Cite|
|
Sign up to set email alerts
|

The proteomic signature of insulin-resistant human skeletal muscle reveals increased glycolytic and decreased mitochondrial enzymes

Abstract: Aims/hypothesis The molecular mechanisms underlying insulin resistance in skeletal muscle are incompletely understood. Here, we aimed to obtain a global picture of changes in protein abundance in skeletal muscle in obesity and type 2 diabetes, and those associated with whole-body measures of insulin action. Methods Skeletal muscle biopsies were obtained from ten healthy lean (LE), 11 obese non-diabetic (OB), and ten obese type 2 diabetic participants before and after hyperinsulinaemic-euglycaemic clamps. Quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
52
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 47 publications
(75 reference statements)
10
52
0
2
Order By: Relevance
“…we use the full pancreas from genetically modified db / db mice. PGAM1 is an enzyme involved in the second phase of glycolysis, although there are some discrepancies as to whether this metabolic pathway is increased or decreased at high concentrations of glucose, it is clear that in T2DM this pathway is disturbed [13,14,15]. At least in type 1 diabetes, it has been demonstrated that multiple alterations in the expression of proteins involved in oxidative stress, aerobic and anaerobic glycolysis and intracellular signaling in human skin were reversed after kidney-pancreas transplant [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…we use the full pancreas from genetically modified db / db mice. PGAM1 is an enzyme involved in the second phase of glycolysis, although there are some discrepancies as to whether this metabolic pathway is increased or decreased at high concentrations of glucose, it is clear that in T2DM this pathway is disturbed [13,14,15]. At least in type 1 diabetes, it has been demonstrated that multiple alterations in the expression of proteins involved in oxidative stress, aerobic and anaerobic glycolysis and intracellular signaling in human skin were reversed after kidney-pancreas transplant [16].…”
Section: Resultsmentioning
confidence: 99%
“…There is controversy on whether the catabolic hexose-processing enzymes, including glucose, decrease or increase in diabetes, as wide alterations have been observed [13,14,15]. …”
Section: Resultsmentioning
confidence: 99%
“…In aging, obesity, and type 2 diabetes, insulin resistance in skeletal muscle has been linked to a number of abnormalities in mitochondrial oxidative metabolism (7,8,9,10). This includes transcriptomic and proteomic evidence of a coordinated downregulation of genes and proteins involved in oxidative phosphorylation (OxPhos) in insulin-resistant skeletal muscle (11,12,13,14) as well as reduced expression of the peroxisome proliferatoractivated receptor gamma coactivator 1 alpha gene (PGC1a), which plays a key role in mitochondrial biogenesis (13,14). The decrease in mitochondrial oxidative capacity has been proposed to cause reduced lipid oxidation with subsequent accumulation of lipids and lipid metabolites, which in turn can inhibit insulin signaling to glucose transport and glycogen synthesis (6,15), as observed in skeletal muscle in obesity and type 2 diabetes (16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, several research groups have performed skeletal muscle proteome analysis from diabetic patients and rodent models of diabetes [68,69,70,71]. These pioneering studies have already begun to advance our understanding of skeletal muscle insulin resistance.…”
Section: Proteome Profiling Of Diabetic Skeletal Musclementioning
confidence: 99%
“…For example, Giebelstein et al showed that the abundance of glycolytic enzymes was up-regulated, while mitochondrial proteins were down-regulated in skeletal muscle from insulin-resistant subjects. Interestingly, these changes were associated with shift in muscle properties towards a fast-twitch pattern [68]. Numerous proteomics studies suggest pivotal role for mitochondrial function in development of Type 2 diabetes.…”
Section: Proteome Profiling Of Diabetic Skeletal Musclementioning
confidence: 99%